Digital Transformation in An Attempt to Revitalize Kabuki Theater Arts - Sujaya, Bella Oktira; Aminah, Shobichatul; Ong, Susy (Journal of Strategic and Global Studies, 2024)
ABSTRACT Kabuki is a traditional performing art that has been present since the end of the Azuchi-Moyama period. In its development, Kabuki has undergone many changes to adapt to the times. This journal discusses the preservation of Kabuki, one of which is carried out through digital transformation. The Japanese government in the early Meiji era considered the preservation of Kabuki to be crucial because it is one of the rich cultural heritages and to attract tourists. This journal uses qualitative research methods obtained from books, documentation, archives, magazines, online mass media, and social media related to the development of Kabuki. With various developments and adjustments to suit tastes, Kabuki performances are preserved. The results of the research show the revitalization of Kabuki through digital transformation, such as Cho Kabuki collaborating with Vocaloid Hatsune Miku and equipped with various advanced technologies such as Kirari, Augmented Reality (AR), Virtual Reality (VR), Mixed Reality (MR), and Extended Reality (XR). These technologies are still being developed to adapt to the tastes and preferences of the present generation.